Lymphocytic vasculitis and oral lesions as exclusive manifestations of the late phase of Covid-19: Case report in an elderly woman (Research, Society and Development, 2022)
Objective: SARS-CoV-2 infection has a wide spectrum of clinical manifestations, and skin lesions associated with infection are increasingly reported, simultaneously with respiratory symptoms or in isolation. Methodology: This is a case report with the purpose of describing and discussing the presented case, with a brief literature review. Results: In this case report, we present an elderly woman, not previously vaccinated for Covid-19, with purpuric lesions on the skin and with a moniliform appearance in the oral cavity, without symptoms or characteristic signs of respiratory infection and positive IgG serology for Covid-19. The histopathological examination of the skin showed vasculitis of small vessels, predominantly lymphocytic, restricted to the superficial dermis. There was laboratory exclusion of etiologies often causing skin lesions similar to the case. Cutaneous manifestations of Covid-19 are addressed, and lymphocytic vasculitis is discussed as a late manifestation of Covid-19. Conclusion: This case highlights the importance of identifying skin lesions associated with Covid-19, for taking appropriate measures to prevent viral transmission.